SOC sequestration affected by fertilization in rice-based cropping systems over the last four decades - Wang, Shuhui; Sun, Nan; Liang, Shuo; Zhang, Shuxiang; Meersmans, Jeroen; Colinet, Gilles; Xu, Minggang; Wu, Lianhai (Frontiers in Environmental Science, 2023)
Enhancing soil organic carbon (SOC) stocks through fertilization and crop rotation will contribute to sustaining crop productivity and mitigating global warming. In this study, we analyzed the differences in SOC stocks and their driving factors in the topsoil (0–20 cm) with various fertilization measures in two rice-based cropping systems (i.e. rice-wheat rotation and double rice rotation systems) over the last four decades from seven long-term experiments in the Yangtze River catchment. The treatments include no fertilizer application (CK), application of chemical nitrogen, phosphorus and potassium fertilizers (NPK) and a combination of NPK and manure applications (NPKM). Results showed that during the last four decades, the topsoil SOC stock significantly increased by 8.6 t ha-1 on average under NPKM treatment in rice-wheat system and by 2.5–6.4 t ha-1 on average under NPK and NPKM treatments in double rice system as compared with CK. A higher SOC sequestration rate and a longer SOC sequestration duration were found in NPKM treatment than that in NPK treatment in both cropping systems. The highest SOC stock ratio (SOC stock in fertilizer treatments to CK) was observed under the NPKM treatment in both cropping systems, though no significant difference was found between these two cropping systems. However, the fertilization-induced relative increase of the SOC stock was 109.5% and 45.8% under the NPK and NPKM treatments, respectively in the rice-wheat system than that in the double rice system. This indicates that the rice-wheat system is more conducive for SOC sequestration. RF and SEM analyses revealed that the magnitude and influencing factors driving SOC sequestration varied between two systems. In the double rice system, continuous flooding weakens the influence of precipitation on SOC sequestration and highlights the importance of soil properties and C input. In contrast, soil properties, C input and climate factors all have important impacts on SOC sequestration in rice-wheat system. This study reveals that the rice-wheat system is more favorable for SOC sequestration despite its lower C input compared to the double rice system in China’s paddies.